ChemInform Abstract: Syntheses and Crystal Structures of New ReO3‐Type‐Derived Transition Metal Oxide Fluorides. Issue 31 (August 2015) - Nakhal, Suliman; Bredow, Thomas; Lerch, Martin
Abstract MNb2O3F6 (M: Mg, Zn), MgM2OF8 (M: Ti, Zr), Fe2TiO8F, and TiNb2O5F4 are prepared by stirring the corresponding phase pure mixed‐metal oxides in a 1:1 mixture of 48% aq.